2011 IEEE 19th International Requirements Engineering Conference 2011
DOI: 10.1109/re.2011.6051649
|View full text |Cite
|
Sign up to set email alerts
|

On human analyst performance in assisted requirements tracing: Statistical analysis

Abstract: Abstract-Assisted requirements tracing is a process in which a human analyst validates candidate traces produced by an automated requirements tracing method or tool. The assisted requirements tracing process splits the difference between the commonly applied time-consuming, tedious, and error-prone manual tracing and the automated requirements tracing procedures that are a focal point of academic studies. In fact, in software assurance scenarios, assisted requirements tracing is the only way in which tracing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 21 publications
(59 reference statements)
2
68
1
Order By: Relevance
“…Kong et al [9] analyzed the process of the traceability validation tasks. Dekhtyar et al [10] confirmed the observation by statistical analysis. The analysis indicates that developers cannot utilize accurate traceability links.…”
Section: Related Workmentioning
confidence: 68%
See 3 more Smart Citations
“…Kong et al [9] analyzed the process of the traceability validation tasks. Dekhtyar et al [10] confirmed the observation by statistical analysis. The analysis indicates that developers cannot utilize accurate traceability links.…”
Section: Related Workmentioning
confidence: 68%
“…As a consequence, a feature location technique with higher recall is a more promising direction. In traceability recovery experiments [8], [9], [10], no significant difference was found between precision and recall. One possible reason for this result is that subjects can understand features in detail during their tasks by reading relevant methods in initial lists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the prior research by one of the authors, concentrated on studying what human analysts do with the results of automated methods and whether they tend to recognize good advice provided by the automated methods [3], [2], [4]. This work indicated that not all trace links are equally easily recognizable by human analysts: some links present in the experimental studies were almost uniformally recovered and recognized by humans, while other links were extremely difficult for them.…”
Section: Introductionmentioning
confidence: 99%